Human Gut-Associated Natural Killer Cells in Health and Disease - Poggi, Alessandro; Benelli, Roberto; Venè, Roberta; Costa, Delfina; Ferrari, Nicoletta; Tosetti, Francesca; Zocchi, Maria Raffaella (Frontiers in Immunology, 2019)
It is well established that natural killer (NK) cells are involved in both innate and adaptive immunity. Indeed, they can recognize molecules induced at the cell surface by stress signals and virus infections. In the gut, their function is much more complex: indeed, they are not precisely organized in lymphoid aggregates, but rather scattered in the epithelium or in the stroma, where they come in contact with a multitude of antigens derived from commensal or pathogenic micro-organisms, beside the components of microbiota. Furthermore, in the bowel NK cells interact with several cell types, including epithelial cells, fibroblasts, macrophages, dendritic cells and T lymphocytes, contributing to the maintenance of the immune homeostasis or to the development of an efficient immune response. Indeed, NK cells have a key role in the response to intestinal bacterial infections, primarily through the production of IFNγ, that can stimulate the recruitment from peripheral blood of additional NK cells leading to the amplification of the anti-bacterial immune response. Nevertheless, NK cells can have a role also in the pathogenesis of gut autoimmune inflammatory bowel diseases (IBD) such as Crohn’s Disease and Ulcerative Colitis. These diseases are considered relevant for the generation of gastrointestinal malignancies. In this regards, it has been evidenced the role of gut-associated NK cells in the immune response to bowel cancers. Thus, in the gut immune system, NK cells play a dual role, as they participate both in physiologic and in pathogenic processes. In this review, we will analyze the known function of NK cells present in the gut mucosa both in health and disease, focusing on the cross-talk among bowel microenvironment, epithelial barrier integrity, microbiota and NK cells.